Analisis Kelayakan Investasi Peternakan Puyuh Petelur - Raharjo, Sapto Budhi, Indah Pratiwi, ST, MT, Hafidh Munawir, ST, M.Eng (2016)
Quail breeders problems in running the business, demand for advanced thinking in order to improve the business or at least be able to maintain business continuity. However, in practice there are several obstacles that egg prices are not fixed. For investment feasibility analysis was done to determine the feasibility. This study aims to determine the feasibility of business investment, Analyze sensitivity and bankruptcy of laying quail farm.Of the Methods used include covering non-financial feasibility analysis: aspects of the market, technical and management. Financial feasibility analysis: NPV, PP, IRR, PI, BEP is then performed a ensitivity analysis and analysis of z-score. The results of a positive NPV calculation is 105 868 500, PP is 3 Months 25 Days, IRR is 41.60%, PI is 1.314 and the BEP is 511 451 eggs. The results of a sensitivity analysis using a fixed feed price scenario 1 egg prices fell 6% worth, while a change of 6.5% is not feasible because of the negative NPV. by using the second scenario the price of feed down the price of eggs remained at 11% worth of 11.5% while the change is not feasible because of the negative NPV. Scenario 3 at the same time feed prices rise in price of eggs dropped by 4% is still feasible, while a change of 4.5% is not feasible because of the negative NPV. And analysis of Altman Z-score for 5 years shows the financial condition of not having financial problems. Z-score of 3.14 the first year. 3.93 the second year, third year 4.28 4.52 fourth year and fifth year 4.70.